Pengaruh Risiko Litigasi dan Tingkat Kesulitan Keuangan Perusahaan terhadap Hubungan antara Konflik Kepentingan dan Konservatisme Akuntansi - Erni Suryandari; Rangga Eka Priyanto (Journal of Accounting and Investment, 2011)
The aim of this research is to examine the effect of interest conflict on accounting conservatism and the effect of litigation risk on the positive relation between conflict of interest and accounting conservatism, and the effect of company’s financial distress on the positive relation between conflict of interest and accounting conservatism.The sample of this research was extracted with purposive sampling method. The populations of this research are all of the manufacturing company, which are listed at Indonesian Capital Market Directory (ICMD). The 125 corporate financial statements were analyzed as a sample. The technique for examining hypothesis is simple regression analysis to examining the first hypothesis and Moderated Regression Analysis (MRA) to examining the second dan the third hypothesis by using SPSS 17.00 program.The results of the research show that: firstly, conflict of interest has a signification positive effect on accounting conservatism. Secondly, litigation risk has a significant positive effect on the positive relation between conflict of interest and accounting conservatism. And the third, company’s financial distress have a significant positive effect on the positive relation between conflict of interest and accounting conservatism.